Pluralitas Agama Dalam Perspektif Permainan: Dialog Antaragama dalam Hermenutika HG Gadamer - Happy Susanto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
The writer tries to analyze the problem of religious plurality through HG Gadamer's hermeneutical analysis. In the article, the writer starts his analysis from the phenomenon of interreligious relationship happens in the world. In the writer's opinion -based on HG Gadamer's analysis-, that human look lost in the phenomenon of hard interreligious relation, on contrary it suggests that the interdependent among religious people. The two categories above don't mean the relation of win or loss, or domination relation, but it is better to say